STUDI PENURUNAN PARAMETER TSS DAN TURBIDITY DALAM AIR LIMBAH DOMESTIK ARTIFISIAL MENGGUNAKAN KOMBINASI VERTICAL ROUGHING FILTER DAN HORIZONTAL ROUGHING FILTER - Imaning Tyas Fitri; Ganjar Samudro; Sri Sumiyati (Jurnal Teknik Lingkungan, 2013)
This study used a combination of vertical roughing filter (VRF) and horizontal roughing filter (HRF) to reduce the content of Total Suspended Solid (TSS) and Turbidity in domestic wastewater. Variations study was only performed on the reactor VRF. Variations used of waste water discharge Q1 = 0.2778 l/hr, Q2 = 0.1389 l/hr, and Q3 = 0.0926 l/hr; and types of media used is charcoal and gravel with coarse size (øӨ20-10 mm), medium (Ө15-6 mm), and fine (Ө10-3 mm). Optimum conditions in the reactor decreased TSS and turbidity at small flow rate or Q3 = 0.0926 l/hr, with a charcoal filter media type, the size of the fine filter media (Ө10-3 mm), with an efficiency of 98,58% and 99,71%.